Efforts to Improve Learning Outcomes of Class X NKN A Students of SMK Negeri 7 Palu on the Material of Chance of an Event Using Media World of Chance - Karangan, Vannesa Novitasari; Hermiyati, Yosepha Endang; Hasbi, Muh (CV. Rayyan Dwi Bharata, 2025)
The use of media in learning is closely related to learning outcomes. As one of the important elements in the learning system, media helps ensure that learning takes place in accordance with the stated objectives. The existence of media support the teaching and learning process to be effective and interesting, so that students can more easily understand the material, which ultimately improves their learning outcomes. This study aims to improve student learning outcomes on the material on the probability of an event through the use of the world of opportunity media. This media is used when delivering material and is given to each group of students to be used during the process and in completing learning questions on the LKPD. Based on the results of the study, it can be concluded that the use of the world of opportunity media on the material on the probability of an event can improve the learning outcomes of class X NKN A students at SMK Negeri 7 Palu, which is evident from the increase in learning outcomes in each cycle.